Reliability of knee joint sonography in the evaluation of gouty arthritis - Anjum Zafar Iqbal; Bacha Raham; Manzoor Iqra; Gilani Syed Amir (Journal of Ultrasonography, 2021)
Objective: To determine the reliability of knee joint sonography in the evaluation of gouty arthritis. Methodology: A search of Google Scholar, PubMed, NCBI, MEDLINE, and Medscape databases, from 1988 up to 2020. The key search terms used were knee joint; knee joint ultrasound; gout; gouty arthritis, knee joint pain; sensitivity; specificity. The reviewer independently screened the titles and abstracts of the relevant articles and full-text downloads to determine whether the inclusion or exclusion criteria were met. Results: In total, 103 articles were identified through the database search. In addition, 11 articles were identified through other sources. Then, screening was performed, and 9 articles were removed due to duplication. Further screening was done for 105 articles, and 27 articles were excluded due to insufficient information. Seventy-eight full-text articles were assessed for eligibility. A total of 13 full-text articles were excluded due to research performed on animals, as the study had been designed as a review of only human studies. Sixty-three studies were included that had a qualitative synthesis. Conclusion: The knee is a weight-bearing joint and may be affected by a myriad of different pathological conditions, therefore a proper diagnosis is of prime importance for a proper management plan. Ultrasound is a non-invasive, radiation-free, and readily available modality that has high sensitivity and specificity in the evaluation of gouty arthritis.